Biotechnological application of methyl-β-cyclodextrin for cholesterol content manipulation in biological membranes - Paliienko, K. O.; Vasylchenko, O. A.; Pastukhov, A. O.; Riabov, S. V.; Borisova, T. A. (Problems of Environmental Biotechnology, 2017)
Investigation is devoted to demonstrate application of methyl-β-cyclodextrin (MβCD) as cargo that attached to magnetic nanoparticles, in particularly maghemite, for the manipulation cholesterol content in synaptic membranes.